Building refurbishment : one step towards sustainable built environment - Bragança, L. (2008)
A sustainable built environment results from the best trade-off between each three dimension of the sustainable development (environment, society and economy). In Western Europe it is usually considered than more than 60% of the buildings to be used in 2050 are already built today and it is expected that the rehabilitation becomes a leading sector in the building industry. To ensure the sustainable rehabilitation of the built environment it is necessary to consider tens of parameters related to the overall impact of the project on the local and global environment as well as preservation of heritage, social trends, economic development, or health and safety of the users. The integration of a huge number of evaluation criteria, some quantitative, other purely qualitative, makes the assessment of such strategy very hard to carry out without a real methodological work. The aim of this paper is to present a multi-criteria decision based methodology that allows the integrated assessment of all different sustainability parameters. The proposed methodology is applied to a case study, which aim is to select the most sustainable solution between different refurbishment scenarios for a building façade.